Pengaruh Expressive Writing Therapy terhadap Self Esteem pada Pasien Skizofrenia di RSJ Dr. Radjiman Wediodiningrat Lawang-Malang - Mustofa, Fathaniah Adila; Wahyuni, Endang Sri (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Abstract Background: Schizophrenia is a chronic mental illness that can affect an individual's quality of life. Individuals with schizophrenia experience a decline in self-functioning, leading to decreased social functioning that impacts self-esteem. Self-esteem is an important aspect for individuals. One non-pharmacological therapy that can be provided is cognitive psychotherapy, specifically expressive writing therapy.Objectives: This research was conducted to determine the effect of expressive writing therapy on self-esteem in schizophrenia patients at RSJ Dr. Radjiman Wediodiningrat Lawang-Malang. Methods: This research is quantitative research with a pre-experimental with a one group pretest-posttest design type. The sampling technique used was purposive sampling with a sample size of 20 people. Self-esteem was measured using the Rosenberg Self-esteem Scale (RSES) Indonesian version instrument. The data analysis technique used is the Paired Sample T-Test. Resulth: The majority of the sample were male (70%); the dominant age category of the sample was early adulthood (35%); unmarried status dominated (55%); the majority were self-employed (50%), and the educational level was high school/vocational school (50%). The average self-esteem score before intervention was 16.60, and after intervention, the average score was 20.15, indicating an increase in scores in the research sample with a difference of 3.5 points. The results of this study, measured using the Paired Sample T-Test, obtained a value of ρ < 0.05 (0.000 < 0.05). Conclusion: This research shows that there is an effect of expressive writing therapy on the self esteem of schizophrenic patients at RSJ Dr. Radjiman Wediodiningrat Lawang-Malang. Keywords : Expressive Writing Therapy, Self-Esteem, Schizophrenia